1999
DOI: 10.1093/jat/23.4.237
|View full text |Cite
|
Sign up to set email alerts
|

The Elimination Profiles of Tenoxicam and Hydroxytenoxicam in Equine Urine and Serum after a 200-mg Oral Dose*

Abstract: Tenoxicam (Mobiflex) was administered orally to four standardbred mares at a dose of 200 mg. Elimination profiles of tenoxicam and hydroxytenoxicam were generated based on quantitation of these analytes in urine and serum by liquid chromatography (LC) with ultraviolet detection. Tenoxicam was confirmed by LC-tandem mass spectrometry daughter ion mass spectra in the last postadministration sample in which tenoxicam was detected. The tenoxicam and hydroxytenoxicam urinary elimination profiles had the same shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Phase II metabolism in the form of β ‐glucuronide conjugation was investigated by hydrolysis with E. coli β ‐glucuronidase enzyme and was found to be negligible. This is consistent with previous results obtained for meloxicam and its metabolites5, 6 and tenoxicam,3 but differs in the case of 5′‐hydroxytenoxicam from the observation of Marland et al ,3 where the equine tenoxicam metabolite was found to be β ‐glucuronide conjugated exclusively. The reason for this discrepancy is not immediately obvious.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Phase II metabolism in the form of β ‐glucuronide conjugation was investigated by hydrolysis with E. coli β ‐glucuronidase enzyme and was found to be negligible. This is consistent with previous results obtained for meloxicam and its metabolites5, 6 and tenoxicam,3 but differs in the case of 5′‐hydroxytenoxicam from the observation of Marland et al ,3 where the equine tenoxicam metabolite was found to be β ‐glucuronide conjugated exclusively. The reason for this discrepancy is not immediately obvious.…”
Section: Resultssupporting
confidence: 92%
“…Analogous fragmentation patterns have previously been reported for the closely related drug meloxicam and its metabolites acquired under the same conditions 5, 6. The positive ion atmospheric pressure chemical ionisation triple quadrupole product ion mass spectra of meloxicam,7 piroxicam7 and tenoxicam3 are also very similar, although prominent fragments in the former two cases deriving from cleavage of the thiazole ring ( m/z 73) and loss of the pyridine ring ( m/z 78), respectively, fall below the fragmentation cutoff of the ion trap and are not seen here. Under negative ion conditions all compounds were deprotonated with ion trap CID resulting only in a loss of sulfur dioxide as reported previously for meloxicam and its metabolites 4…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The pharmacological actions of these oxicams are related to inhibition of cyclooxygenase (Cox), a key enzyme of prostaglandine biosynthesis at the site of inflammation [1]. Several methods have been reported for determination of piroxicam and tenoxicam including spectrophotometry for PX [2][3][4][5][6][7][8][9][10] and for TX [11][12][13][14], chromatography, electroanalytical and physicochemical methods for PX [15][16][17][18][19][20] and for TX [21][22][23]. Among the various methods available for the determination of drugs, spectrophotometry continues to be very popular, because of its simplicity, specificity and low cost.…”
Section: Introductionmentioning
confidence: 99%